Psychometric Evaluation of the Learning Agility Scale–Short (LAS-S) for Indonesian Teachers - Hafnidar Hafnidar; Fakhria Ulya; Ulfina Vanissa (International Journal of Pedagogy and Learning Community (IJPLC), 2026)
Rapid changes in educational systems require teachers to continuously learn and adapt to evolving professional demands. Learning agility has therefore emerged as a critical psychological capacity supporting teacher effectiveness. This study aimed to evaluate the psychometric properties of the Indonesian version of the Learning Agility Scale–Short (LAS-S) adapted for teachers. A quantitative psychometric approach was employed involving 150 Indonesian teachers selected through random sampling. The adapted instrument consisted of 25 items representing four dimensions of learning agility: mental agility, people agility, change agility, and result agility. Data were analyzed using item discrimination analysis and internal consistency reliability testing. The results indicated that all items demonstrated acceptable to high discrimination indices, and the scale showed excellent internal consistency, with a Cronbach’s alpha coefficient of .94. These findings suggest that the Indonesian LAS-S is a reliable instrument for assessing learning agility among teachers. The availability of this measure provides a foundation for research and policy initiatives aimed at strengthening teachers’ adaptive learning capacities.